Identifying developmental challenges of youth with congenital heart defects: A patient‐oriented perspective. (25th August 2022) - Bolduc, Marie‐Eve; Rennick, Janet E.; Gagnon, Isabelle; Sokol, Eva; Brossard‐Racine, Marie; Majnemer, Annette
Abstract: Background: Youth with congenital heart disease (CHD) are at high risk for a range of developmental impairments that become evident at different times across childhood and adolescence. This study aimed to explore perspectives of youth with CHD with respect to their developmental follow‐up across childhood. Methods: Interpretive description was used as a methodological approach for this qualitative study. Youth aged 12–22 years with CHD requiring open‐heart surgery before 2 years of age and who had received health services in Canada since birth were enrolled. Results: Ten youth with CHD, two males and eight females, aged 13–22 years (mean 19.8) participated in this study. With higher social and academic demands as well as increased level of autonomy associated with older age, some youth faced new challenges that they had not encountered as children. Youth with CHD identified four aspects of the continuum of care as needing to be changed to better respond to their needs. First, the format of developmental follow‐up needs to be adapted to their unique challenges. Second, resources must be more easily accessible throughout childhood and adolescence. Third, planning for transition to adult care is essential to ensure continuity of services. Finally, they identified that the school system is an essential component of the continuum of care. Conclusions: Adolescents and young adults with CHD are at high risk of developing physical, academic and psychosocial challenges; however, timely identification of challenges does not appear to be optimal across domains and transition points, from the perspective of the youth themselves. Youth with CHD reported not having the resources and supports they required to optimize their functioning. Our findings suggest that several approaches could be adopted to enhance identification and outcomes to address the limitations of current Canadian practices.